2017
DOI: 10.1002/lom3.10169
|View full text |Cite
|
Sign up to set email alerts
|

Convective mixing and high littoral production established systematic errors in the diel oxygen curves of a shallow, eutrophic lake

Abstract: The diel (24‐h) oxygen (O2) curves approach has become a popular method for analyzing gross primary production (GPP) and ecosystem respiration (ER) rates in aquatic systems. Despite the simplicity of this approach, there remain aspects of the calculation and interpretation of diel O2 curves which may skew results, with potentially large implications for estimates of metabolic rates. One common problem in lakes is the occurrence of unexpected changes in O2 concentrations (for instance, increasing overnight O2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Increased DO in the late evening DO as well as negative GPP and R values may also have resulted from advective transport of DO (cf Staehr et al., ). Brothers, Kazanjian, Köhler, Scharfenberger, and Hilt () also found that littoral production and horizontal advection established systematic errors in the diel DO profiles of a shallow, eutrophic lake, a phenomenon that may explain the observed diurnal asymmetry between DO evolution and PAR in WL.…”
Section: Discussionmentioning
confidence: 93%
“…Increased DO in the late evening DO as well as negative GPP and R values may also have resulted from advective transport of DO (cf Staehr et al., ). Brothers, Kazanjian, Köhler, Scharfenberger, and Hilt () also found that littoral production and horizontal advection established systematic errors in the diel DO profiles of a shallow, eutrophic lake, a phenomenon that may explain the observed diurnal asymmetry between DO evolution and PAR in WL.…”
Section: Discussionmentioning
confidence: 93%
“…convection (Farmer, 1975;Jonas et al, 2003;Mironov et al, 2002) and downslope gravity currents, the latter originating from differential heating in the shallows (Kenney, 1996;Kirillin et al, 2015). In lakes, these currents transport heat and biogeochemical tracers between nearshore and the interior basin (Brothers et al, 2017;Encinas Fernández et al, 2016;Farrow, 2004), supporting the biogeochemical connectivity between littoral and pelagic zones. Under-ice gravity currents have been observed, and their transport has been implicated in the basin-scale thermal structure and circulation of polar lakes (Cortés & MacIntyre, 2019;Kirillin et al, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…Allochthonous C is known to drive CO 2 emission in small and shallow ponds, owing to their high perimeter to volume ratio (Finlay et al ; Holgerson ; Wilkinson et al ). Other possible factors that may explain the discrepancy between the measured CO 2 emission and estimated internal CO 2 production include inaccurate estimates of oxygen saturation and gas transfer velocity, as well as a possible underestimation of daytime respiration (Del Giorgio and Williams ; Staehr et al ; Brothers et al ). Estimating respiration rates per organism group is a difficult practice as well and comes with several uncertainties and caveats (Del Giorgio and Williams ; Martínez‐García et al ), which was confirmed by the fact that our modeled ER only accounted for roughly half of the oxygen diel‐curve–derived ER.…”
Section: Discussionmentioning
confidence: 99%